2013
DOI: 10.1093/ejcts/ezt376
|View full text |Cite
|
Sign up to set email alerts
|

Early chest tube removal after video-assisted thoracic surgery lobectomy with serous fluid production up to 500 ml/day

Abstract: Our findings suggest that chest tube removal after VATS lobectomy is safe despite volumes of serous fluid production up to 500 ml/day. The proportion of patients who developed pleural effusion necessitating reintervention was low (2.8%), and a complication of the reintervention was seen in only 1 patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 14 publications
1
57
2
1
Order By: Relevance
“…In recent years several studies on early chest tube removal from the pleural cavity following pulmonary resection and cardiac surgery have been published. Bjerregaard et al 6 reported it was safe to remove chest tubes despite drainage of 450 mL/day after lobectomy by video-assisted thoracic surgery. Xie et al 1 performed a prospective randomized study and found that a 300 mL/day volume threshold for chest tube removal after video-assisted thoracic surgery lobectomy was feasible and safe and that a 450 mL/ day volume threshold for chest tube removal increased the risk of thoracentesis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years several studies on early chest tube removal from the pleural cavity following pulmonary resection and cardiac surgery have been published. Bjerregaard et al 6 reported it was safe to remove chest tubes despite drainage of 450 mL/day after lobectomy by video-assisted thoracic surgery. Xie et al 1 performed a prospective randomized study and found that a 300 mL/day volume threshold for chest tube removal after video-assisted thoracic surgery lobectomy was feasible and safe and that a 450 mL/ day volume threshold for chest tube removal increased the risk of thoracentesis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, drainage systems have only been compared with relation to postoperative air leak (11)(12)(13)(14)(15). Whilst this is an important aspect of the decision to remove chest tubes, the volume of fluid extracted is another major determinant, that continues to garner increased attention amongst research circles (2,(16)(17)(18). Pleural fluid formation is greatly influenced by pleural permeability and shift in oncotic and hydrostatic pressures.…”
Section: Discussionmentioning
confidence: 99%
“…250 ml/Tag als Grenze für die Entfernung der Thoraxdrainagen gesehen. Große Studien konnten jedoch nachweisen, dass Fördermengen zwischen 450 und 500 ml/Tag nicht automatisch zu einer erhöhten Inzidenz an interventionsbedürftigen Pleuraergüssen führten und daher akzeptiert werden können [3,7,8]. In einer prospektiven Studie konnte zusätzlich gezeigt werden, dass eine postoperative Manipulation am Drainageschlauch ("milking") zu einer vermehrten Fördermenge der Pleuradrainage ohne klinische Verbesserung führt und daher nicht empfohlen wird [9].…”
Section: Drainagemanagement Nach Lungenoperationenunclassified